Gambaran Kasus Forensik Klinik di RSUP Prof. Dr. R. D. Kandou Manado Tahun 2022 - Pratiwi Hardani; Erwin Kristanto; Nola T. S. Mallo (Universitas Sam Ratulangi, 2024)
Abstract: To date, there is lack of available data regarding clinical forensic services in Indonesia, including North Sulawesi. Prof. Dr. R. D. Kandou Hospital in Manado, a referral center in North Sulawesi, was chosen as the research location expecting to obtain the description of clinical forensic cases in North Sulawesi. This study aimed to obtain a description of clinical forensic cases in North Sulawesi in 2022. This was a descriptive study with a cross sectional design. The resukts showed that the cumulative number of clinical forensic cases at Prof. Dr. R. D. Kandou Hospital in 2022 was 250 cases, consisting of 155 cases of traffic accidents, 59 cases of abuse, and one case of sexual violence. Victims consisted of 79% male sand 21% females. Most clinical forensic cases came to Prof. Dr. R. D Kandou Hospital in December (15%) and the least in April (3%). Most of the wound locations were found in the abdominal area (65%), followed in the back area (34%), and the least in the vaginal area (1%). In conclusion, traffic accidents were the most common clinical forensic cases in North Sulawesi. Most injuries were found in the abdominal area and the least in the genital area. Most of the victims were male. December 2022 donated the most clinical forensic cases. Only a few cases of sexual violence were brought to Prof. Dr. R. D. Kandou Hospital, therefore, the victims still need to be outreached and encouraged to report. Keywords: sexual violence; assault; traffic accidents; clinical forensic cases Abstrak: Hingga saat ini masih belum banyak data yang tersedia mengenai kasus pelayanan forensik klinik baik di Indonesia maupun Sulawesi Utara. RSUP Prof. Dr. R. D Kandou Manado sebagai pusat rujukan di Sulawesi Utara dipilih menjadi lokasi penelitian karena diharapkan dapat menggambarkan kasus forensik klinik di Sulawesi Utara. Penelitian ini bertujuan untuk memperoleh gambaran kasus forensik klinik di Sulawesi Utara pada tahun 2022. Jensi penelitian ialah deskriptif dengan desain potong lintang. Hasil penelitian mendapatkan angka kumulatif kasus forensik klinik di RSUP Prof. Dr. R. D. Kandou sepanjang tahun 2022 sebanyak 250 kasus, terdiri atas 155 kasus kecelakaan lalu lintas, 59 kasus penganiayaan, dan satu kasus kekerasan seksual. Korban terdiri atas 79% berjenis kelamin laki-laki dan 21 % perempuan. Kasus forensik klinik tertinggi pada bulan Desember (15%) dan paling sedikit pada bulan April (3%). Lokasi luka terbanyak ditemukan pada area abdomen (65%), disusul daerah punggung belakang (34%), dan paling sedikit daerah vagina (1%). Simpulan penelitian ini ialah kasus forensik klinik terbanyak di Sulawesi Utara terjadi pada jenis kelamin laki laki, jenis kasus kecelakaan lalu lintas, dan lokasi luka di bagian abdomen. Bulan Desember menyumbangkan kasus forensik klinik terbanyak. Kasus kekerasan seksual masih sedikit yang dibawa ke RSUP Prof. Dr. R. D. Kandou sehingga masih memerlukan sosialisasi dan dorongan agar korban berani melapor. Kata kunci: kekerasan seksual; penganiayaan; kecelakaan lalu lintas; kasus forensik klinik